Epidemiological differentiation of pathogenic strains of Salmonella enteritidis by ribotyping. - Landeras, E (1996)
The usefulness of two-way ribotyping, performed with SphI and PstI, as a genetic marker for a series of pathogenic Salmonella enteritidis strains is reported. Eighteen combined ribotypes were differentiated, a discrimination index of 0.77 was reached, a genetic relationship dendrogram was traced, and the results were applied in an epidemiological study.